EXPLANATORY STUDY: THE IMPACT OF TRUST IN KASKUS ON KASKUSERS PURCHASE INTENTION - Aditya Lukmanjaya (CALYPTRA, 2014)
Big potential market in Virtual Communities (VCs) make Consumer to Consumer (C2C) websites focusing on increasing their customer bases by converting members of their VCs into C2C buyers and sellers. This phenomenon is called e-commerce based on social network (ESN). One of Indonesia’s website which apply ESN is Kaskus. The objective of this study is to propose a framework on the understanding of how trust in Kaskuser and trust in www.kaskus.co.id or vendors in Kaskus affect purchase intention. A questionnaire was adopted from Lu et al. (2010) for online survey. Non probability sampling method is used for collecting data. The sample consisted of 210 registered member of Kaskus. Data were analiyzed through descriptive statistics, SPSS, and LISREL. Result of the study finds the positive impact of trust in Kaskus on Kaskuser’s purchase intention. All antecedents of trust are proved have postive impact on both trust in members and trust in website/vendor’s which lead to intention to get information, and purchase intention thereafter. However, trust in Kaskuser shows negative impact on www.kaskus.co.id or trust in vendors. In addition, from all antecedents of trust, structural assurances has the greatest impact into Kaskuser’s purchase intention.